2000
DOI: 10.1042/cs0980495
|View full text |Cite
|
Sign up to set email alerts
|

Short-term analysis of the relationship between blood pressure and urinary sodium excretion in normotensive subjects

Abstract: The aim of this study was to investigate whether, in the short term, physiological blood pressure changes are coupled with changes in urinary sodium excretion in normotensive subjects, maintained at fixed sodium intake and under controlled postural and behavioural conditions. Twelve normotensive subjects were recruited. For each subject, seven urine samples were collected at fixed time intervals during an overall 26 h period: late afternoon (16.00-20.00 hours), evening (20.00-24.00 hours), night (24.00-06.00 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Clinical studies show that the day:night variation in BP is strongly correlated with renal sodium excretion. 9 The kidney is an important long-term regulator of BP and impaired pressure natriuresis may contribute to nocturnal hypertension 10 : BP remains elevated during sleep to facilitate sodium excretion and maintain 24-hour sodium balance. 11 , 12 Certainly, hypertensive and prehypertensive patients have a blunted day:night pattern of sodium excretion and excrete a greater fraction of their daily output at night.…”
mentioning
confidence: 99%
“…Clinical studies show that the day:night variation in BP is strongly correlated with renal sodium excretion. 9 The kidney is an important long-term regulator of BP and impaired pressure natriuresis may contribute to nocturnal hypertension 10 : BP remains elevated during sleep to facilitate sodium excretion and maintain 24-hour sodium balance. 11 , 12 Certainly, hypertensive and prehypertensive patients have a blunted day:night pattern of sodium excretion and excrete a greater fraction of their daily output at night.…”
mentioning
confidence: 99%
“…First, the two most widely used methods for evaluating sodium intake are 24‐hour urine sodium collection and dietary recall. The results of the one‐time spot urine sodium method may be biased by circadian variations in the blood sodium concentrations in the general population and in CKD patients . To compensate for this potential limitation, we evaluated the mean of the three most recent spot urine sodium concentrations to estimate the daily sodium intake in CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the pressure-natriuresis relationship is blunted during upright posture, possibly because of the activation of neurohumoral systems. 8 Staessen et al 9 also observed that both systolic and diastolic blood pressure correlate with sodium excretion only during sleep. Staessen et al 10 went on to show that office systolic and diastolic blood pressures also correlated positively with nighttime sodium excretion, and Dyer et al 11 found the same relationship using a night/day sodium excretion ratio.…”
mentioning
confidence: 93%